2016
DOI: 10.48084/etasr.665
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of a Multilevel Parallel Hybrid Active Power Filter

Abstract: This paper introduces a new control approach for the Multilevel Parallel Hybrid Active Power Filter (M-PHAPF) which can compensate harmonics and variable reactive power demand of loads by controlling the DC link voltage adaptively in medium voltage applications. By the means of this novel control method, M-PHAPF obtains a better and more efficient performance in the compensation of harmonics and reactive power compared to when using conventional control methods. The performance and stability of the proposed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Generally, a SAPF consists of three main blocks: the power device block, the reference current calculation block, and the power switches control block. From the literature review, it is found that several typologies of SAPF filters have been invented during the last years [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a SAPF consists of three main blocks: the power device block, the reference current calculation block, and the power switches control block. From the literature review, it is found that several typologies of SAPF filters have been invented during the last years [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Several hybrid APF (HAPF) topologies are introduced in [2-10, 13] for reactive power and harmonic current filtering. The most common topologies are shunt HAPF (SHAPF) [4][5][6][7][8][9][10][11][12] consisting of an APF and a passive filter connected in series with each other and series HAPF [3] which is a combined system of the shunt passive filter and a series APF. An extensive overview of the topological structures is given in [2,13].…”
Section: Introductionmentioning
confidence: 99%
“…Most articles describe research focused on low voltage levels. On the contrary, Multilevel SHAPF (M-SHAPF) [6][7][11][12] is the most often used in medium voltage levels in industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation